Firm-productivity and export under non-constant marginal costs - Mukherjee, Arijit (Economics Bulletin, 2017)
Recent theoretical research shows that exporters are more productive than non- exporters. We show that this result holds almost trivially for the case of a constant marginal cost of production, as mainly assumed in the literature, but it may not hold true if the marginal cost is not constant. Our result provides a simple explanation for recent empirical evidence showing exporters can be less productive than non- exporters.